Memaknai Alam Semesta: Simbolisasi Kosmik dalam Ontologi Mistik Sahl ibn ‘Abd Allāh al-Tustarī - Moh. Anwar Syarifuddin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2009)
This piece explicates mystical interpretation conducted by the Sufi Sahl ibn Abd Allah al-Tustari on certain Qur’anic verses illustrating cosmic symbols of the Sufi ontology. In this symbolic interpretation the understanding of natural phenomena given in the form of analogy that is more psychologically oriented, for example, earth that is signified as “heart” which is low in nature because of its engagement with the matter referred to be a symbol of “darkness”. On contrary, the sky is interpreted as an element of height that belongs to the role of “enlightening”. The symbolism of the universe that is signified with its psychic understanding is the main ideas Sahl Tustari’s mystical ontology that centers around the mystical concept of the light of Muhammad, which has vast influence within the development of Islamic mystical thought in later period. The main inquiry of the present paper is what kinds of metaphysical concepts described by Sahl al-Tustari in his mystical interpretation to the Qur’anic verses illustrating the natural phenomena? Discussion begins with earth as the symbol of lowliness, then explaining the sky as symbols of the natural representation of the higher world. Filling the gap between the contested cosmological concepts Sahl Tustari offers his mystical concept of the light of Muhammad that becomes an intermediary channel for the lowly position of man in his way back to God.